Pemanfaatan Rompong Tenaga Surya melalui Program Kosabangsa di Desa Pomolulu - Spetriani; Sitti Sabariyah; Taufik Ihsan; Bakhrani A Rauf; Darmawang; Faizal Amir (LPPI UMN AL WASHLIYAH, 2026)
The Kosabangsa Program in Pomolulu Village was implemented to address the low productivity and income of fishers due to traditional fishing methods. This program aimed to improve the capacity and welfare of fishers through the application of solar-powered fish aggregating devices (FADs). The method used was participatory training consisting of counseling and hands-on practice, including the introduction of FAD concepts, solar energy systems, and training on assembly, installation, and operation in the field. The results showed an implementation of FAD technology significantly improved fish catches, increasing fishers’ income from approximately IDR 3,000,000 per month to more than IDR 6,750,000 within a 10-day group harvest period. The program also enhanced technical skills and group collaboration in managing the technology. Therefore, the application of solar-powered FADs through a training-based approach proved effective in improving productivity, capacity, and welfare of fishers. This program is expected to be sustainable through institutional strengthening and continuous assistance.